Independent mental health advocacy : the right to be heard : context, values and good practice /: the right to be heard : context, values and good practice. (2015) - Newbigging, Karen; Ridley, Julie; McKeown, Mick; Sadd, June; Machin, Karen; Cruse, Kaaren; De La Haye, Stephanie; Able, Laura; Poursanidou, Konstantina
No abstract available